Development of a Nanocellulose Composite Based Voltammetric Sensor for Vitamin B9 Analysis - Ghalkhani, Masoumeh; Shahrokhian, Saeed (Current Nanoscience, 2016)
Background: As a B group vitamins, vitamin B9 is a Water-soluble vitamin which is produced by plants and microorganisms (bacteria and yeasts). Vitamin B9 plays an important role in the production of proteins and nucleic acids in body and also is one of the substances that prevents the development of neural tube defects in the fetus. Methods: Electrochemical behavior of vitamin B9 was studied using a potentiostat/galvanostat SAMA 500, electroanalyzer system, I. R. Iran. A three-electrode system was used, including a glassy carbon working electrode (d = 2.0 mm, purchased from Azar Electrode Co., Urmia, I.R. Iran), an Ag/AgCl (saturated KCl) reference electrode and a Pt wire auxiliary electrode. Electrochemical impedance spectroscopy (EIS) measurements were performed with a Potentiostat /Galvanostat/Frequency response analyser (FRA) EG model 273A. Scanning electron microscopy (SEM) experiments were performed on a VEGA TESCAN scanning electron microscope (Czech Republic). Results: An electrochemical sensor for vitamin B9 was developed by deposition of carbon nanoparticles-cellulose nanofibers (CNP-CNF) suspension on the GCE surface. Voltammetric experiments revealed good adherence of thin layer coating of CNP-CNF to the GCE surface which enhanced long-time stability and repeatability of modified electrode responses. Voltammetry results showed distinguish enhancement of vitamin B9 anodic peak current (27 fold) on the surface of CNP-CNF/GCE compared to the bare GCE. High uniform and quite porous structure formed on the surface of GCE through drop casting of CNP-CNF suspension produced very large active surface area which effectively improved characteristics of the electrode surface toward diffusion of electroactive species. Based on AFM measurements, the thickness of CNP-CNF layers was estimated below 100 nm. SEM image indicated the presence of nanoparticles on the GCE surface along with displaying uniform distribution of nanoparticles on the electrode surface. The average size of nanoparticles deposited on the GCE was estimated below 100 nm. Under the optimized conditions, CNP-CNF/GCE exhibited a wide linear dynamic range of 0.1 – 10 μM for the voltammetric determination of vitamin B9. The modified electrode was successfully applied for the accurate determination of vitamin B9 amounts in pharmaceutical preparations. Conclusion: The CNP-CNF modified glassy carbon electrode showed notable electrochemical advantages for vitamin B9 analysis such as high accuracy, good repeatability and reproducibility as well as low detection limit and wide linear range. Results of electrochemical investigations revealed that introducing the CNP-CNF to the electrode surface increased electroactive area and leaded to significant enhancement of oxidation peak current of vitamin B9. Therefore, it can be concluded that the prepared modified electrode has great potential to accurate analysis of vitamin B9 in pharmaceutical and clinical preparations.
Keywords: cellulose